Pediatric Respiratory Infections: Case Based Learning - Marta King (Association of American Medical Colleges, 2011)
Abstract Respiratory infections account for the majority of pediatric illnesses. They can present with varied severity and in numerous settings. The purpose of this activity is to use real-life cases to discuss phone, outpatient, and inpatient approaches to pediatric patients who present with common respiratory complaints: apnea and cyanosis, wheezing, stridor, cough, and sore throat. For each case, one participant takes on the role of the patient or parent and is provided with the final diagnosis and further case details. Other participants are divided into one of four groups: concerned parent call, outpatient clinic, emergency room, and inpatient. All of the cases progress through three different settings; more information is available based on passage of time and change in setting. Throughout the case, participants come up with and narrow down a differential diagnosis list based on additional information. At the conclusion of each case, key learning points are summarized. Additional possible discussion points are listed in the instructor guide and can be included based on the group. This module was initially created as a pediatric resident medium-sized-group board-review activity, but it can be easily adapted to other learners and settings. Since the module's creation, it has been successfully used with family medicine residents, third-year medical students, ward teams, and night float rotations in both medium- and small-group settings. The activity itself tends to be fun and very interactive. Feedback has been very positive. Learners have specifically commented on appreciating the real-life scenarios, working through clinical problems as a group, and discussions regarding medical decision making. The handouts have been noted as being helpful for clerkship and in-service exam preparation.